Implementasi Kurikulum Merdeka Belajar di MA Nahdlatul Ulama’: Putri Wulandari, Muhammad Lutfi* - Wulandari, Putri; Lutfi, Muhammad (Samudra Publisher, 2024)
The purpose of this study is to investigate the implementation of the